Maqosid Syariah Sebagai Dasar Sistem Ekonomi Berkeadilan - Khodijah Ishak (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2013)
The economic principle that is prescribed in Islam is not to live luxuriously, not trying to work banned, pay zakat and riba away, is the sum of the creed, moral and Islamic sharia as the reference in the development of an Islamic economic system. Moral values ​​not only by the activity of the individual but also the collective interaction, even the relationship between the individual and the collective can not dichotomize. Individual and collective value than ever that should always be present in the development of the system, there are a tendency especially moral values ​​and practices that put the interests of the collective than individual interests. Preferences of both the individual and the collective economy of the Islamic economy finally has its own character with a distinctive form of activity. Umer Chapra and offers basic principles of Islamic economics, there are three aspects are as follows: a). Ness, b). Caliphate and c). Justice. The three principles are inseparable, interrelated due to the creation of a good and stable interconnected economy. Theology (God) should be used to reflect the purpose of sharia among others; fulfilment of needs (needs fulfilment), appreciated source of income (respectable source of earnings), income distribution and welfare evenly (equitable distribution of income and wealth) as well as the stability and growth (growth and stability).